2019
DOI: 10.1111/den.13542
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐guided needle‐based confocal laser endomicroscopy in gastrointestinal subepithelial lesions: Feasibility study

Abstract: Background and Aim: Needle-based confocal laser endomicroscopy (nCLE) allows for real-time optical biopsies during endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA). Little is known about nCLE imaging of gastrointestinal subepithelial lesions (GI-SEL); therefore, we determined its feasibility.Methods: We carried out EUS, nCLE, and finally FNA in 25 patients with GI-SEL between November 2015 and December 2018. We retrospectively compared nCLE findings with pathological findings of EUS-FNA or surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…A recent prospective multicenter study of 206 patients with pancreatic cystic lesions showed thay sensitivities and specificities of nCLE for the diagnosis of serous cystadenomas, mucinous cystic neoplasms, and premalignant cystic lesions were all 0.95 or higher; the area under the receiver operating characteristic curve was significantly larger for nCLE than for cyst fluid carcinoembryonic antigen or EUS [ 80 ]. A number of studies also evaluated the feasibility and safety of nCLE for the assessment of solid organs (i.e., solid pancreatic lesions, lymph nodes, and SELs) [ 81 , 82 , 83 ]. Although in vivo real-time imaging using nCLE is highly concordant with pathology and may replace ROSE, it is important to keep in mind that EUS-FNA alone has a sensitivity around 90% for malignancy.…”
Section: The Use Of Through-the-needle Imagingmentioning
confidence: 99%
“…A recent prospective multicenter study of 206 patients with pancreatic cystic lesions showed thay sensitivities and specificities of nCLE for the diagnosis of serous cystadenomas, mucinous cystic neoplasms, and premalignant cystic lesions were all 0.95 or higher; the area under the receiver operating characteristic curve was significantly larger for nCLE than for cyst fluid carcinoembryonic antigen or EUS [ 80 ]. A number of studies also evaluated the feasibility and safety of nCLE for the assessment of solid organs (i.e., solid pancreatic lesions, lymph nodes, and SELs) [ 81 , 82 , 83 ]. Although in vivo real-time imaging using nCLE is highly concordant with pathology and may replace ROSE, it is important to keep in mind that EUS-FNA alone has a sensitivity around 90% for malignancy.…”
Section: The Use Of Through-the-needle Imagingmentioning
confidence: 99%